Good Tourism Governance in the Development of Heritage Tourism (Case Study: Europeesche Champ in the Old Town of Surabaya): Good Tourism Governanace dalam Pengembangan Heritage Tourism (Studi Kasus Europeesche Champ Kota Lama Surabaya) - Lestari, Dyah; M. Husni Tamrin (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
This research aims to analyze the development of Heritage Tourism in the European Area (Europeesche Champ) of Kota Lama Surabaya using the perspective of Good Tourism Governance with descriptive qualitative methods and a case study approach. Data collected through interviews, observation and documentation and analyzed using the theory of Good Tourism Governance. The results of the study show that good tourism governance is very important for the development of heritage tourism as an area that has cultural heritage potential which is the attraction of tourist destinations and opens opportunities for local economic growth. Good Tourism Governance in the European Area (Europeesche Champ) Kota Lama Surabaya can be said to have been implemented well with the success of 5 out of 10 indicators, namely related community participation, sustainable resource utilization, environmental carrying capacity, environmental accountability, and promotion and advocacy of local cultural values. However, there is still room for improvement in the indicators of stakeholder involvement, local ownership partnerships, accommodating community aspirations, program monitor and evaluation, and community training.